The Improvement of Community Empowerment in Handling Children with Malnutrition Through Participatory Rural Appraisal Method in Kupang City - Irlin Falde Riti (Humanistic Network for Science and Technology (HNST), 2017)
Health Office of Kupang City commits program for handling children and family nutrition such as Family Aware Nutrition program, Breastfeeding Companion Food, Supplementary Feeding but it has not been maximal. This can be seen from the number of malnutrition cases in Kupang city in 2013 wherein 288 children or 2.27% suffering malnutrition, in 2014 the number of malnutrition cases in Kupang City decreased to 207 children or 0.33% and in 2015 the number of malnourished children were 204 children or 1.05%. The method of this research is qualitative. Informant in this research were 6 nutrition officers. Obtained information that Public Health Center of Kupang City had not tried to empower the community well in handling children malnutrition therefore needed a better effort to make community involved in overcoming the malnutritional problems of children by following the stages of empowerment namely the determination of territory, socialization, community awareness, organizing, implementing activities, and building networksTime New Roman 10 regular, single line spacing, paragraph: justified aligment. Keywords: two to six words. Keywords: Marasmus, Kwashiorkor, Family Aware Nutrition Program, Breastfeeding Companion Food